O uso do teatro como ferramenta para ampliar a sensibilização e promover o (re)posicionamento do sujeito da escola pública: putting yourself in someone elses' shoes - Aline Xavier Pinheiro (2020)
The present work is focused on the use of theater in English classes in a public school aims to investigate whether the dramatization based on the choice of themes, focused on the issues of conflict, violence, citizenship, oppression and social justice, contributes to the (re)positioning of the subject before society. This way, from the theatrical games proposed by Viola Spolin (2008) and Augusto Boal (1993), we seek to introduce the theater in a playful way in order to incite the interest of public school English students in relation dramatization. In the same way, we carried out a survey with the students, in order to identify the themes related to conflict issues that would most encourage them to express their opinions, in a way of respect in contact with each other and promoting their own (re) positioning. Based on the model of a qualitative research, our work is anchored in the method of pedagogical intervention. The resonances that echo in the rhetoric of the subjects participating in this research were considered, (SERRANI-INFANTE, 2001) as well as the enunciative heterogeneities (AUTHIER REVUZ, 1990, 2004) and the marks that constitute them as subjects who are often crossed by the speech of the other, thus creating the false illusion of having their own and homogeneous speech. The research consisted of scene diaries written by the students during the process and also 2 questionnaires applied at the be ginning and at the end of the interventions. Through the analysis of the words of the students in this research, it was possible to perceive, in some of these participants, an awareness in relation to the topics covered, which allowed us to bring them up for discussion and prepare short scenarios, in order to provide an opportunity of repositioning to the students involved in the process. In broad terms, we could conclude that the theater has the ability to modify the subject and his actions in relation to the other. We also found, through some reports from the students, that once they are expressing themselves in English, they allow themselves to get closer to each other overcoming the barrier of shyness. We understand, therefore, that the enactment in English allows the subject to change even more, since he distances himself from his mother tongue when dressing up as a character who expresses himself in another language.